A Research on the Perception of Architecture Students about Straw-Bale Buildings - Erbil, Yasemin; Yücel, Çiğdem; Tuğba Kızılkuşak, R. (European Journal of Sustainable Development, 2018)
Although straw-bale construction has been used for thousands of years, currently doesn?t attract considerable attention by professional architects and students. The reason behind this is assumed to be the prejudices and lack of knowledge about straw-bale buildings. In the scope of this research understanding candidate architects point of view on the preference criterias that are effective about choice of straw-bale construction is aimed. For this purpose, among 214 students of private university (in Turkey) in 2015-2016 academic year, 100 students were selected through simple random sampling and the survey was conducted. The results show that according to the candidate architects, the properties such as its being compatible to nature, harmless to human health, recyclable and low-cost are the main positive qualities of straw-bale construction, whereas lifetime, structural properties and fire resistance are still calling into question. This study demonstrates that straw bale construction techniques, which have the potential to solve environmental problems, need to be given more attention in the architecture educational. Keywords: Straw-bale construction, preference criterias, architecture students